Ceftriaxone resistance and genes encoding extended-spectrum ß-lactamase among non-typhoidal salmonella species from a tertiary care hospital in Kuala Lumpur, Malaysia - Karunakaran, R.; Sun, T. T.; Rahim, F. F.; Bee, B. L.; Sam, I. C.; Kahar-Bador, M.; Hassan, H.; Puthucheary, S. D. (Institute of Infectious Diseases, 2012)
The prevalence of ceftriaxone resistance and the associated genes encoding extended-spectrum ß-lactamase (ESBL) was determined in 149 non-duplicate non-typhoidal Salmonella isolated in 2008–2009 from patients in a tertiary care hospital in Kuala Lumpur, Malaysia. The resistance rate to ceftriaxone was 2.7z (2/74) in 2008, 4.0z (3/75) in 2009, and 3.4z (5/149) overall. CTX-M ESBL genes were detected in 2 of the 5 ceftriaxone-resistant isolates. The prevalence of ceftriaxone resistance, although low, is a concern because it limits therapeutic options. Continued surveillance of ceftriaxone resistance is important to monitor its trends